Filicide-suicide: An unusual variant of dyadic death. (March 2019) - Ateriya, Navneet; Saraf, Ashish; Kanchan, Tanuj; Meshram, Vikas P; Singh Shekhawat, Raghvendra; Setia, Puneet
Dyadic suicides may be committed simultaneously or one after another by two or more people who may or may not have made a prior pact. The perpetrator is usually male and their victims female, and generally their intimate partners, with children less commonly involved. Another distinct type of homicide-suicide is the killing of children by a parent (filicide-suicide). The terms 'maternal filicide' or 'paternal filicide' are used respectively when the perpetrator is the mother or the father of the victim. We report a rare case of maternal filicide, where the mother drowned her three children and then herself in the same water tank. The case highlights the extreme stress put on a mother of girls in a patriarchal society where there is an overriding expectation and wish for sons. The resulting pressure on this mother for her 'failure' caused her to take her own and her children's lives.